2015
DOI: 10.1378/chest.14-1174
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Defect in Club Cell Secretory Protein Attenuates Airway Inflammation in COPD

Abstract: In vitro, rhCCSP exogenous supplementation can reverse CSE-induced IL-8 release in biopsy specimens from patients with COPD, indicating a potential use of this strategy in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
1
56
0
Order By: Relevance
“…CC16 polymorphism and local deficiency on the one hand, and a decreased number of club cells on the other hand, were reported as features of COPD [8,9], as confirmed by LAUCHO-CONTRERAS et al [10] in the current issue of the European Respiratory Journal. In previous studies, exogenous CC16 showed pharmacological properties that could decrease excess airway inflammation and mucus production in ex vivo models [11][12][13]. However, CC16 has not demonstrated physiological properties, as shown in a prior report on CC16-deficient mice, which were not more susceptible to changes induced by cigarette smoke [14].…”
mentioning
confidence: 90%
“…CC16 polymorphism and local deficiency on the one hand, and a decreased number of club cells on the other hand, were reported as features of COPD [8,9], as confirmed by LAUCHO-CONTRERAS et al [10] in the current issue of the European Respiratory Journal. In previous studies, exogenous CC16 showed pharmacological properties that could decrease excess airway inflammation and mucus production in ex vivo models [11][12][13]. However, CC16 has not demonstrated physiological properties, as shown in a prior report on CC16-deficient mice, which were not more susceptible to changes induced by cigarette smoke [14].…”
mentioning
confidence: 90%
“…Moreover, plasmid-mediated over-expression of CC16 in the nasal epithelium of CC16 −/− mice reduces their increased release of IL-8 when IL-1β is administered 113 . Gamez et al reported that epithelial cells isolated from COPD airways produce more IL-8 compared with cells isolated from healthy smoker and non-smoker airways, and this increased release of IL-8 was reduced by adding rCC16 to the COPD cell cultures 114 . Also, rCC16 reduces LPS- or IL-13-stimulated production of IL-8 (and also MUC5AC) by human bronchial epithelial cells 115 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 99%
“…The rCC16 treatments inhibited MUC5AC and IL-8 expression ( Figure 3 ) and reduced activation of NFκB and extracellular signal-regulated kinase (ERK1/2) in the IL-13- or LPS-activated cells. Gamez et al showed that rCC16 inhibited the CSE-induced release of IL-8 from bronchial epithelial cells isolated from COPD patients 114 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 99%
“…8 Gamez et al 2 show that CCSP secretion is reduced in cultured bronchial epithelial cells from patients with COPD, which also release more CXCL8. 2 Furthermore, recombinant human CCSP (rhCCSP) restores the increase in CXCL8 induced by exposure to cigarette smoke-conditioned medium back to normal. In addition to CCSP, club cells also secrete a secretory component of IgA, which is also reduced in COPD and may be a factor in bacterial colonization of the airways in COPD.…”
mentioning
confidence: 99%
“…1 Moreover, we know that the administration of inappropriate initial antibiotic therapy for VAP, usually due to the presence of multidrug-resistant bacteria as the causative pathogens, is associated with greater hospital mortality and longer hospital lengths of stay. 2 Th ese outcome-infl uencing characteristics of VAP make it an important infection for intensivists to manage in an optimal manner. Such optimal management requires ICUs and hospitals to have consensus-derived strategies in place for the prevention, diagnosis, and treatment…”
mentioning
confidence: 99%